Integrating Instructional Supervision and School Leadership to Enhance Teacher Performance - Yuliza (BRIDGE : The Multidisciplinary Research Portal, 2024)
This study examines the implementation of principal supervision in improving teacher performance at MTs Mathla’ul Anwar Landbaw, Gisting, Tanggamus Regency, using an interdisciplinary perspective that integrates educational management, school leadership, and educational psychology. Employing a qualitative descriptive approach, data were collected through structured interviews with the principal and teachers, classroom observations, and document analysis. The findings indicate that principal supervision is conducted systematically through planning, implementation, and follow-up stages, and is applied using directive, non-directive, and collaborative approaches according to teachers’ needs. The results show that principal supervision contributes to improvements in teacher performance across four competency dimensions: professional, pedagogical, social, and personal. The most prominent improvements are observed in professional and pedagogical competencies, particularly in subject mastery, lesson planning, instructional implementation, and reflective practices. From a theoretical standpoint, the findings reinforce the role of instructional supervision as a leadership mechanism that enhances teacher self-efficacy and professional development. Practically, the study highlights the importance of strengthening principals’ supervisory capacity through communicative, reflective, and collaborative supervision practices to support continuous teacher development. Despite its contributions, this study is limited by its focus on a single madrasah and reliance on participants’ perceptions. Future research is recommended to involve multiple educational institutions and employ mixed-methods approaches to enhance the generalizability of findings.